Europe's “Shadow Agent”: Rethinking Ukraine's Historical Role in the 20th Century - Hrabovskyi, Serhii; Grabovska , Iryna (Skhid, 2025)
The article is devoted to the problem of adequately understanding the role of Ukraine and the Ukrainian nation in European being. The authors focus not on economic, cultural, and scientific factors, which are also important, but on geopolitical and military-political factors. The article describes and analyzes the most important moments of active participation of Ukrainians in events that are extremely important for the whole of Europe. To this end, the authors use the concepts of active and latent geopolitical subjectivity, national subject, and actor. They introduce the concepts of “shadow agent” and “pulsating subjectivity” into scientific discourse for the theoretical understanding of the role of Ukraine and Ukrainians in the events of the 20th century. With their help, the authors seek to reveal as deeply as possible the essence of the “key moments” in European history to which Ukraine is directly involved. These include the destruction of the despotic Russian Empire in 1917, the halting of the Bolshevik invasion of Western Europe in 1920, and active participation – from September 1, 1939, to September 2, 1945 in combat operations against the totalitarian states of the Axis, the liquidation of the Gulag, and, ultimately, the dismantling of the USSR. The article concludes that throughout the 20th century, Ukraine and Ukrainians repeatedly played one of the key roles on the “geopolitical chessboard,” either as an active player or as a shadow actor, and if they had not done so, Europe would now look much worse, and European civilization might even have dissolved into the Eurasian geopolitical swamp. However, the real role of Ukraine and Ukrainians was not always recorded, so it seemed that historically significant events took place, but without Ukraine. Therefore, the authors note: “bringing” Ukraine “out of the shadows,” showing the whole world, and above all Europe, its true historical value as an integral factor, and often even the savior of European civilization, is today one of the most pressing tasks of the Ukrainian intellectual elite, including scholars of Ukrainian studies.